Integrasi Nilai Spiritual dan Intelektual dalam Hadits Tarbawi: Telaah Epistemologis terhadap Tujuan Pendidikan Islam - Muhammad Rifkhi Maulana; Ainul Gani; Muhammad Akmansyah; Amirudin Amirudin (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study examines the integration of spiritual and intellectual values in Tarbawi Hadith with a focus on epistemological analysis of the aims of Islamic education. The background of this research is the dichotomy of knowledge in modern education systems that separates religious sciences from general sciences, leading to a spiritual crisis and moral degradation. The Prophet’s hadiths, especially those contained in the book Riyadhus Shalihin by Imam an-Nawawi, contain integrative messages between strengthening reason (intellectual) and purifying the soul (spiritual). This study aims to epistemologically analyze tarbawi hadiths about the obligation to seek knowledge, the virtue of reason, and the purification of the soul and their relevance to the aims of contemporary Islamic education. Using a qualitative approach with library research and thematic hadith analysis (maudhu’i), this research traces hadiths from the book Riyadhus Shalihin chapters on the virtue of knowledge and the etiquette of seeking knowledge. The results show that tarbawi hadiths teach balance between spiritual dimensions (tazkiyah al-nafs) and intellectual dimensions (ta’lim al-’aql). The aim of Islamic education from the hadith perspective is not merely knowledge transfer but the formation of insan kamil (perfect human beings) who are intellectually intelligent and morally noble. This study recommends strengthening the integration of spiritual and intellectual values in the Islamic education curriculum as a response to the challenges of the Society 5.0 era.